Performance of Chilli (Capsicum annuum L.) hybrids for yield and quality traits: Chilli hybrids for yield and quality - Verma, Vinay; Vikram, Amit; Sharma, Yash Pal; Bhardwaj, Ramesh K; Dogra, Rajesh K; Gupta, Meenu; Singh, Shalini (Journal of Spices and Aromatic Crops, 2022)
Twenty-eight F1 combinations of chilli (Capsicum annuum L.) obtained from half-diallel cross along with eight diverse parents were evaluated in a field study to elucidate the information on the extent of mean performance of various horticultural traits. The analysis revealed that all the genotypes possessed wide spectrum of variability and showed significant differences for parents and hybrids for the traits studied. For parents UHF CHI 13 (216.20), UHF CHI 15 (193.80), UHF CHI 5 (139.00) and for hybrids H1 (182.60), H9 (181.40) and H7 (172.80) hold highest fruit count per plant. The parents UHF CHI 5 (1047.13 g), UHF CHI 15 (949.62 g) and UHF CHI 7 (912.61 g) and cross combinations H17 (1535.10 g), H8 (1320.00), H6 (1229.76) and H18 (967.60) recorded the high ripe fruit yield per plant. As for earliness, parents UHF CHI 5 (43.33), UHF CHI 11 (45.00), UHF CHI 7 (45.33) and hybrids H27 (42.67), H26 (43.00) and UH28 (43.00) took minimum days for flowering. For pungency UHF CHI 12 (0.28%), UHF CHI 13 (0.26%), DKC-8 (0.24%) and H23 (0.33%), H5 (0.31%), H26 (0.26%) recorded high capsaicin content.